2003
DOI: 10.1034/j.1399-6576.2003.00042.x
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesiologists in prehospital care make a difference to certain groups of patients

Abstract: The diagnostic pattern among emergency ambulance users included all main groups of diseases. After the MECU fewer were brought to hospital. The overall mortality for all ambulance users was not influenced by the MECU. For the subgroups, especially AMI, mortality was lower after the introduction of the MECU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 9 publications
2
25
1
Order By: Relevance
“…At the same time, Christensen et al found an anaesthesiologist manned ground ambulance reduced the number of hospitalisations in a Danish urban EMS system. 13 It can be speculated that there is an overall health benefit by reducing hospitalisation of patients, and rendering the special medical resources available for those needing them most, whether in rural or urban areas. Somers et al [14][15][16][17] also support the role of GPs in prehospital emergency medicine, but address the need of improving skills needed to deal with emergencies and disasters.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, Christensen et al found an anaesthesiologist manned ground ambulance reduced the number of hospitalisations in a Danish urban EMS system. 13 It can be speculated that there is an overall health benefit by reducing hospitalisation of patients, and rendering the special medical resources available for those needing them most, whether in rural or urban areas. Somers et al [14][15][16][17] also support the role of GPs in prehospital emergency medicine, but address the need of improving skills needed to deal with emergencies and disasters.…”
Section: Discussionmentioning
confidence: 99%
“…3 In Aarhus, an anaesthesiologist staffed mobile emergency care unit (MECU) is called in addition to an ambulance to life threatening cases, including acute coronary syndrome (ACS). 4 The MECU enables us to achieve an early provisional diagnosis.We wanted to study the accuracy of dispatch of the MECU to acute coronary syndrome (ACS) cases. ACS was used as an example of a life threatening emergency.…”
mentioning
confidence: 99%
“…The staffing of ambulances with physicians who are trained to care for cardiopulmonary unstable patients and who are well accustomed to perform invasive procedures in this setting might improve the quality of care in prehospital emergency medicine 1 2 11. Klemen and Grmec12 studied the care for severe traumatic brain injury and compared the outcomes of patients treated by EMT or emergency physicians, and showed that patients treated by emergency physicians had a reduced rate of death on admission, hospital mortality in more severely injured patients and better functional neurological outcomes.…”
Section: Discussionmentioning
confidence: 99%